2000
DOI: 10.1097/00007890-200006150-00023
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine Stress Echocardiography in Patients Undergoing Liver Transplantation Evaluation

Abstract: In patients with low to moderate risk of cardiac disease, DSE performed as part of an evaluation for liver transplantation is a poor predictor of major perioperative events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
85
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 8 publications
4
85
0
Order By: Relevance
“…Results with dobutamine stress echocardiography have shown poor sensitivity and low negative predictive value, partially because of an inability to reach target heart rate. 2,12,13 Most of these patients are on b blockers to decrease portal hypertension and prevent esophageal bleeding. Ideally, a noninvasive test should be highly sensitive to diagnose CAD in potential transplantation patients, considering the perioperative cardiovascular complication risks involved with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Results with dobutamine stress echocardiography have shown poor sensitivity and low negative predictive value, partially because of an inability to reach target heart rate. 2,12,13 Most of these patients are on b blockers to decrease portal hypertension and prevent esophageal bleeding. Ideally, a noninvasive test should be highly sensitive to diagnose CAD in potential transplantation patients, considering the perioperative cardiovascular complication risks involved with the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They found a sensitivity of 100%, specificity of 90%, positive predictive value of 100%, and negative predictive value of 100% for DSE. Finally, Williams et al, 32 after excluding all patients with known CAD or symptoms suggestive of CAD, studied low-to moderate-risk patients with 1 or more cardiac risk factor with DSE and found a negative predictive value of only 86%.…”
Section: Screening For Cad In Patients With Esldmentioning
confidence: 99%
“…Clearly, positive and negative results with screening DSE become more significant as patients with known cardiac disease or more cardiac risk factors are included. The study of Williams et al 32 showed that the inclusion of lower risk patients diminished the value of a negative DSE result. Therefore, the dilemma is who to screen.…”
Section: Screening For Cad In Patients With Esldmentioning
confidence: 99%
“…12 According to Williams and associates, DSE positivity is not correlated with intraoperative cardiac events. 13 However, a normal stress test has a high negative predictive value (> 90%) in patients who are undergoing LT. 14 Nuclear myocardial perfusion scintigraphy (MPS) is also used for determining cardiac risk and eligibility for LT. Coronary vasodilating agents (dipyridamole or adenosine) are used during this test. Nuclear cardiac involvement during rest and maximal exercise are compared to evaluate ischemia.…”
Section: Introductionmentioning
confidence: 99%